Nephroprotective effect of virgin coconut oil in Plasmodium berghei ANKA infected Balb/c mice - Syafarinah Nur Hidayah Akil; Heny Arwati; Puspa Wardhani; Priangga Adi Wiratama (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2021)
AbstractMalaria is a parasitic infectious disease caused by Plasmodium, which remains a world health problem with an estimated 219 million cases worldwide. In severe malaria infection, several organs of the body can be affected, including the kidneys. One of the pathophysiology associated with the worsening of this disease is oxidative stress. The use of antioxidants is expected to prevent this, and one product that has a high antioxidant content is virgin coconut oil (VCO). This study aimed to analyze the effect of VCO on the kidney in Plasmodium berghei ANKA-infected mice. This study was an in vivo laboratory experimental study with a randomized post-test only control group design using 35 BALB/c mice infected with P. berghei ANKA, weighing 20-30 grams. VCO with the Javara® brand is used with doses of 1, 5, and 10 ml/kg body weight (kgBW)/ day. The parameter assessed were levels of BUN, creatinine, and renal histopathological changes. The administration of VCO on the treated group shows minimal tubular necrosis and glomerulonephritis compared to the negative control group. The BUN and creatinine levels in the treated group were also lower than the negative control group. The results showed that VCO has a nephroprotective effect against P. berghei ANKA infection in mice.Keywords: malaria, kidney, virgin coconut oil